Phage Therapy as a Promising New Treatment for Lung Infection Caused by Carbapenem-Resistant Acinetobacter baumannii in Mice - Hua, Yunfen; Luo, Tingting; Yang, Yiqi; Dong, Dong; Wang, Rui; Wang, Yanjun; Xu, Mengsha; Guo, Xiaokui; Hu, Fupin; He, Ping (Frontiers in Microbiology, 2018)
Carbapenem¬-resistant Acinetobacter baumannii (CRAB) which is noted as a major pathogen associated with healthcare-associated infections has steadily developed beyond antibiotic control. Lytic bacteriophages with the characteristics of infecting and lysing specific bacteria have been used as a potential alternative to traditional antibiotics to solve multidrug-resistant bacterial infections. Here, we isolated A. baumannii-specific lytic phages and evaluated their potential therapeutic effect against lung infection caused by CRAB clinical strains. The combined lysis spectrum of four lytic phages’ ranges was 87.5% (42 of 48) against CRAB clinical isolates. Genome sequence and analysis indicated that phage SH-Ab15519 is a novel phage which does not contain the virulence or antibiotic resistance genes. In vivo study indicated that phage SH-Ab15519 administered intranasally can effectively rescue mice from lethal A. baumannii lung infection without deleterious side effects. Our work explores the potential use of phages as an alternative therapeutic agent against the lung infection caused by CRAB strains.